2018
DOI: 10.1002/mde.2917
|View full text |Cite
|
Sign up to set email alerts
|

Better innovators or more innovators? Managerial overconfidence and corporate R&D

Abstract: We use 3 measures of managerial overconfidence: the press coverage of chief executive officers, his/her age, and his/her experience in the industry. Our results show that the firms run by overconfident managers actually invest more in R&D expenditures, even after controlling for country, industry, and time factors. Overconfident managers not only spend more on R&D but also amplify the effect of financial determinants of R&D such as firm liquidity or profitability. Nevertheless, overconfident managers do not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 98 publications
(122 reference statements)
1
8
0
Order By: Relevance
“…Wang, Sutherland, Ning, Wang, and Pan (2018) suggest that overconfident managers show a strong level of “internal locus of controls” over corporate decision‐making. The positive impact of MO on R&D investments has been verified in Europe (e.g., Zavertiaeva, López‐Iturriaga, & Kuminova, 2018) and China (e.g., Wang et al, 2018). Vietnam is the only emerging country that we know little.…”
Section: Introductionmentioning
confidence: 94%
“…Wang, Sutherland, Ning, Wang, and Pan (2018) suggest that overconfident managers show a strong level of “internal locus of controls” over corporate decision‐making. The positive impact of MO on R&D investments has been verified in Europe (e.g., Zavertiaeva, López‐Iturriaga, & Kuminova, 2018) and China (e.g., Wang et al, 2018). Vietnam is the only emerging country that we know little.…”
Section: Introductionmentioning
confidence: 94%
“…The research results showed that there is a significant relationship between overconfidence and firm financial performance. Zavertiaeva et al (2018) study the influence of chief executive officers' overconfidence on corporate research and development (R&D). They find that overconfident managers not only spend more on R&D but also amplify the effect of financial determinants of R&D such as firm liquidity or profitability.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…A higher value of financial performance is usually positively connected to managers' confidence under the existence of the "self-serving attribution bias," and managers will take responsibility of firms' success [45]. It is suggested that managers' confidence or overconfidence could result in high risk-taking decisions such as R and D actions [46]. In summary, a higher value of financial performance means more available resources and firms are prone to take more risks.…”
Section: Moderating Effect Of the Value Of Financial Performancementioning
confidence: 99%